On a Discrete-Time Risk Model with Random Income and a Constant Dividend Barrier - Zhenhua Bao; Junqing Huang; Jing Wang (Journal of Mathematics)
In this paper, a discrete-time risk model with random income and a constant dividend barrier is considered. Under such a dividend policy, once the insurer’s reserve hits the level bb>0, the excess of the reserve over b is paid off as dividends. We derive a homogeneous difference equation for the expected present value of dividend payments. Corresponding solution procedures for the difference equation are invested. Finally, we give a numerical example to illustrate the applicability of the results obtained.